Leadership Models in Islamic Boarding Schools to Improve Literacy Supervision - Zakki, Mohammad; Naim, Ngainun; Akhyak, Akhyak; Aziz, Abd. (PT. Riset Press International, 2025)
The development of Islamic boarding schools is seen from the number of students and members of the community who study Islamic religious knowledge. Students themselves can understand Islamic teachings perfectly thanks to the support of a culture of reading and writing developed and facilitated by the kiai as the main manager in the Islamic boarding school. The role of the kiai does not stop at the form of support and provision of facilities, but also has a high interest and habit in reading and writing. This leadership model inspires a culture of reading and writing in the Islamic boarding school environment. This research is qualitative supported by a phenomenological approach. Data collection techniques include in-depth interviews, participant observation, and documentation. Data analysis was then conducted, including data condensation, data presentation, and conclusion drawing. Data validation was conducted through credibility, transferability, defendability, and confirmability tests. This research focuses on the supervision model developed by the kiai at the Al Falah Islamic Boarding School. The supervision model implemented by the Al Falahh Islamic is inspired by the leadership of the kiai as the primary administrator of the Islamic boarding school, over the structural officials within the Annuqayah area. It also inspires supervision by the library manager through coordination with other regional libraries. It also includes internal and external supervision in selecting students' writings before publication. It also includes supervision within the educational institution.